Collected stories - Sillitoe, Alan 1928-2010 (Flamingo, 1995)
Thirty-eight stories on life among the English working classes. They include The Loneliness of the Long Distance Runner, on a rebellious youth in a reformatory, and Mr. Raynor the School Teacher, on a teacher who is a Peeping Tom.